THE OUTCOME OF MEDICO-LEGAL CASES IN A TERTIARY HEALTH CENTER OF MID-GUJARAT REGION IN INDIA - Rathod, Beejaysinh G; Pathak, Akhilesh K (Journal of Forensic Medicine and Toxicology, 2019)
In developing countries like India, Medico-Legal Cases (MLC) are registered by different modes, but the majority of them are registered through the emergency department of a hospital. In these cases, treating doctor is having medical as well as legal duties. The analysis of the MLC and its outcome in the tertiary health center is helpful for better management of these cases as well as allocating the resources and funds to handle the cases in an improved way. The present study was done at a tertiary health center of the Mid-Gujarat region in India with the aim to know the outcome of the MLC cases to improve future management.
Keywords: Medicolegal case; Forensic medicine; Emergency Department; Death; Resource allocation; Implementation